2009
DOI: 10.1016/j.rmed.2008.10.003
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity C-reactive protein in the exhaled breath condensate and serum in stable and unstable asthma

Abstract: The levels of hs-CRP in EBC are correlated with those measured in serum and may provide another useful diagnostic tool for detecting and monitoring low-grade inflammation in patients with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 33 publications
1
44
0
Order By: Relevance
“…These results were confirmed by our previous report, in which the increase in hs-CRP levels both in serum and EBC and the correlation of this parameter with F ENO and ECP in asthmatic patients were revealed [32]. However, Rosias et al [33] were not able to demonstrate the presence of CRP in the EBC of asthmatic children and healthy controls.…”
Section: Discussionsupporting
confidence: 86%
“…These results were confirmed by our previous report, in which the increase in hs-CRP levels both in serum and EBC and the correlation of this parameter with F ENO and ECP in asthmatic patients were revealed [32]. However, Rosias et al [33] were not able to demonstrate the presence of CRP in the EBC of asthmatic children and healthy controls.…”
Section: Discussionsupporting
confidence: 86%
“…It is possible that the chronic airway inflammation can contribute to a systemic inflammatory response, leading to atherosclerosis. 25,26 In a cross sectional study, Vijayakumar et al 27 reported that patients with bronchial asthma are twice as likely to develop arterial inflammation than control subjects with low Framingham risk scores without asthma. Asthma may activate the expression of bronchoalveolar coagulation, and further impair the procoagulant activities and attenuate fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
“…High sensitivity CRP, a systemic marker of low-grade inflammation has been negatively correlated with pulmonary function tests (FEV1) ( r = −0.49, p = 0.01) and positively associated with percent eosinophils (r = 0.44, p=0.03) in induced sputum from asthmatics (Allam et al, 2009) as well as an increased frequency of airway hyperresponsiveness (Ridker et al, 1997). While some studies in adult asthmatics demonstrate that hs-CRP in serum is correlated with hs-CRP in EBC (r = 0.74 in stable asthma treated with inhaled corticosteroids, p=0.0003) as well as exhaled nitric oxide (r = 0.62, p = 0.004) (Zietkowski et al, 2009), other studies do not find this relationship (Sutherland et al, 2007). Overlapping lines of evidence in asthmatics (Navratil et al, 2009; Takemura et al, 2006) and those with chronic obstructive pulmonary disease (Sin and Man, 2006; Dahl et al, 2001) suggest that while systemic and airway inflammation may be correlates of one another, they may also operate independently in influencing lung structure and function.…”
Section: Linking Stress Immunomodulation Respiratory Function and mentioning
confidence: 99%